PERLINDUNGAN NEGARA TERHADAP HAK KONSTITUSIONAL ANAK TERLANTAR DI INDONESIA - Zulfahmi '; Dodi Haryono; Emilda Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Children's rights are an essential part of the human rights contained in the 1945 and the United Nations convention on the rights of the child , therefore we have to fix the whole issue of children as contained in the Convention on the right of the child which has been ratified since 1980 , based on Child Rights Convention in general, Neglected children‟s who for some reason his parents neglect and or unable to perform his duties so that a child needs both physical , spiritual and social are not met . Neglected children are children aged 5-18 years who for some reason so can not with reasonable basic needs whether physical , spiritual , and social . The purpose of this thesis namely : The First , How to setup the constitutional rights of abandoned children in the laws and regulations in force in Indonesia ,the second , how the scope of the constitutional rights of abandoned children in Indonesian , three advantages and disadvantages constitutional right settings waif in laws and regulations applicable in Indonesian . the research can be classified in this type of normative legal research or also called doctrinal legal research . Definition of normative legal research or legal research is the research doctrinal document library or study . From the research, there are three main things that can be inferred that , the First , How to setup the constitutional rights of abandoned children in the laws and regulations in force in Indonesia , the second , how the scope of the constitutional rights of abandoned children in Indonesian , the third , advantages and disadvantages setting the constitutional rights of abandoned children in the laws and regulations applicable in Indonesia . Suggestions of the author , the first , the Government at the time of policy or legislation should be to the benefit of and impartially to the problem of abandoned children because no matter what they as the people of Indonesian . This function to maintain the state of abandoned children will be realized in solved. The second , to overcome the problem of abandoned children can be done in the following way : given shelter / home school education for abandoned children , free education of abandoned children , and welfare facilities the people of the state need to be improved , increase access to scholarships , increase learning system , balance of learning , play , achieve, maintain and appreciate the creativity of children , families empowering . Keywords : Protection of Constitutional Rights – State - Neglected Children